2010
DOI: 10.1210/en.2009-1302
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Inhibition of Human Scavenger Receptor Class B Type I Gene Expression by Glucocorticoid in Adrenal and Ovarian Cells

Abstract: Scavenger receptor class B type I (SR-BI) facilitates the reverse transport of excess cholesterol from peripheral tissues to the liver via high-density lipoproteins. In steroidogenic tissues, SR-BI supplies cholesterol for steroid hormone production. We show here that the transcription of the human SR-BI gene is subject to feedback inhibition by glucocorticoid in adrenal and ovarian cells. SR-BI mRNA levels were increased in adrenals from corticosterone-insufficient Crh(-/-) mice, whereas corticosterone replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…In further support of the notion that cholesterol delivered via scavenger receptor BI to the adrenals is a rate-limiting factor in adrenocortical glucocorticoid production, Mavridou et al [14] have now also shown that the expression of scavenger receptor BI in adrenocortical cells is subject to negative feedback control by glucocorticoids. They identified a glucocorticoid-responsive element in the proximal promoter of human scavenger receptor BI that confers repression of transcription upon treatment with the synthetic steroid dexamethasone.…”
Section: Scavenger Receptor Bi and Adrenal Steroidogenesismentioning
confidence: 84%
See 1 more Smart Citation
“…In further support of the notion that cholesterol delivered via scavenger receptor BI to the adrenals is a rate-limiting factor in adrenocortical glucocorticoid production, Mavridou et al [14] have now also shown that the expression of scavenger receptor BI in adrenocortical cells is subject to negative feedback control by glucocorticoids. They identified a glucocorticoid-responsive element in the proximal promoter of human scavenger receptor BI that confers repression of transcription upon treatment with the synthetic steroid dexamethasone.…”
Section: Scavenger Receptor Bi and Adrenal Steroidogenesismentioning
confidence: 84%
“…by Mavridou et al [14], thus, suggest the involvement of the nuclear glucocorticoid receptor in the repression of scavenger receptor BI transcription. The exact mechanism behind the glucocorticoid-mediated negative feedback on scavenger receptor BI expression, however, remains to be established, as Sporstøl et al [15] have previously shown repression of scavenger receptor BI expression by dexamethasone in human HepG2 cells that exhibit very low glucocorticoid receptor expression levels.…”
Section: Key Pointsmentioning
confidence: 87%
“…Interestingly, apoAI and apoAII, two major protein constituents of HDL, are differentially regulated by dexamethasone, with the first having its hepatic expression elevated and the latter decreased [38]. Scavenger receptor class B type I was found to be down-regulated by glucocorticoids in adrenal and ovarian cells [39]. …”
Section: Discussionmentioning
confidence: 99%
“…199 Glucocorticoids suppress SR-BI expression, thus exerting another negative feedback action by reducing the adrenal gland synthesis of glucocorticoids. 200,201 As a consequence of these actions of glucocorticoids, plasma ACTH concentrations are high in patients with Addison's disease and are low in patients with Cushing's syndrome caused by a cortisol-secreting adrenal tumor or exogenous glucocorticoid administration.…”
Section: Glucocorticoid Negative Feedbackmentioning
confidence: 99%